Analysis of the Marketing Strategy for the Young Indonesian Hajj Savings Product at PT. Bank Syariah Indonesia KCP Medan Sukaramai - Harahap, Faiza Shakira Saina; Rokan, Mustapa Khamal; Anggraini, Tuti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The waiting list for the hajj pilgrimage in Indonesia continues to grow longer from year to year. This has led to the emergence of alternative methods of saving for the hajj pilgrimage, Bank Syariah Indonesia presents the Indonesian young hajj savings. However, competition in the hajj savings product market is very tight because many other Islamic banks also offer the same product. Therefore, the author wants to analyze the marketing strategy of the Indonesian young hajj savings product to see if the product is able to compete in the market and assess the various efforts that BSI has made in attracting the attention of potential customers. This study uses a qualitative method using a descriptive and observational approach. Data collection techniques in this study are observation, interviews, and literature studies. In addition, researchers use descriptive analysis techniques. The findings of this study are that Bank Syariah KCP Medan Sukaramai uses the Segmentation, Targeting, and Positioning (STP) approach to determine who the marketing target is for the Indonesian young hajj savings product, implementing the marketing strategy for the Indonesian young hajj savings product is to conduct socialization to Muslim school institutions, companies, and Muslim organizations. Furthermore, online promotion through social media and technology. And the next strategy is to educate parents who have children under 17 years old to save early through the Indonesian young hajj savings at BSI KCP Medan Sukaramai.